(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Inappropriate drug usage is a global health issue, particularly in developing nations like India. Irrational drug use has a negative impact on both health and medical expenses. Prescription auditing is a crucial method for raising the standard of prescriptions, which raises the standard of care provided. The current study was conducted to evaluate the rational use of pharmaceuticals for completeness, readability, and against the key drug use indicators specified by the World Health Organization (WHO). Material and methods: In the surgery department, 300 prescriptions were chosen at random from the medical records for a cross-sectional retrospective analysis, regardless of the patient’s diagnosis or characteristics. The WHO core drug use indicators, medical components, and general information were assessed for each prescription. Using Microsoft Excel, the collected data were tallied and shown as descriptive statistics. SPSS version 25 was used for analysis. Results: General information is included with every prescription. 67 percent of prescriptions were written under a generic name, while 85.6% of prescriptions included the diagnosis. On average, 11.45 prescription drugs were written. In 53.8% of prescriptions, the clinical examination was mentioned; however, in 94% of prescriptions, the history of allergy was not included. Conclusion: According to WHO-recommended parameters for quality improvement, our study emphasises the necessity of providing our prescribing physicians with detailed prescription writing training.